2020
DOI: 10.1016/j.omtn.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobically Modified let-7b miRNA Enhances Biodistribution to NSCLC and Downregulates HMGA2 In Vivo

Abstract: MicroRNAs (miRNAs) have increasingly been shown to be involved in human cancer, and interest has grown about the potential use of miRNAs for cancer therapy. miRNA levels are known to be altered in cancer cells, including in non-small cell lung cancer (NSCLC), a subtype of lung cancer that is the most prevalent form of cancer worldwide and that lacks effective therapies. The let-7 miRNA is involved in the regulation of oncogene expression in cells and directly represses cancer growth in the lung. let-7 is there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…As it pertains to precision medicine for cancer treatment, detection of genetic aberrations is the basis of developing effective treatment options. 30 -32 Through the analysis of genetic mutations in patients with cancer, we can tailor the treatment plan for each patient with cancer to maximize the curative effect, minimize the damage, and optimize the resources. 33 -36…”
Section: Precision Medicine and Tumor Gene Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it pertains to precision medicine for cancer treatment, detection of genetic aberrations is the basis of developing effective treatment options. 30 -32 Through the analysis of genetic mutations in patients with cancer, we can tailor the treatment plan for each patient with cancer to maximize the curative effect, minimize the damage, and optimize the resources. 33 -36…”
Section: Precision Medicine and Tumor Gene Detectionmentioning
confidence: 99%
“…29 As it pertains to precision medicine for cancer treatment, detection of genetic aberrations is the basis of developing effective treatment options. [30][31][32] Through the analysis of genetic mutations in patients with cancer, we can tailor the treatment plan for each patient with cancer to maximize the curative effect, minimize the damage, and optimize the resources. [33][34][35][36] Next-Generation Sequencing and Precise Targeting Therapy for Tumors Next-generation sequencing, also known as large-scale parallel sequencing, can simultaneously sequence millions or even billions of DNA molecules, achieving the goal of large-scale, high-throughput sequencing.…”
Section: Precision Medicine and Tumor Gene Detectionmentioning
confidence: 99%
“…In aggressive breast cancer cell lines, it was shown that polyarginine-PNA conjugated anti-miR-221 was specific for miR-221, and demonstrated efficient cellular uptake without the aid of transfection reagents [57]. Segal et al found that hydrophobically modified miRs (hmiR) added directly to culture medium or subcutaneously can enhance the biodistribution of the miRNAs in NSCLC [60].…”
Section: Systemic Deliverymentioning
confidence: 99%
“…The rapid clearance of naked RNAs leads to a short life and instability. Chemically engineered miRNA modifications would be necessary to protect miRNAs from degradation and promote long-lasting potency (Segal et al, 2020). On the other hand, potential off-target effects of miRNAs (due to the imperfect complementarity with the 3' UTR of target genes) might cause undesirable silencing of other genes, potential toxicity, and reduced therapeutic efficacy.…”
Section: Perspectives and Challenges Of Developing Therapeutic Micrornasmentioning
confidence: 99%